Development and Validation of Sleep Disturbance Questionnaire in Patients with Acute Coronary Syndrome. (22nd October 2014) - Sepahvand, Elham; Jalali, Rostam; Khaledi Paveh, Behnam; Rezaei, Mansour
Abstract : Background and Objectives . Severe sleep disturbance is a common problem among patients in cardiac care units (CCUs). There are questionnaires to measure sleep disturbances. Therefore, the present study seeks to design a valid and reliable questionnaire to assess sleep disturbance in patients with acute coronary syndrome (ACS) hospitalized in CCUs. Materials and Methods . In the present methodological research, items of the questionnaire were extracted through a systematic review. The validity and reliability of the questionnaires was assessed by face validity, content validity, construct validity, Cronbach's alpha coefficient, and test-retest methods. Results . Factor analysis provided a questionnaire of 23 items on 5 dimensions of sleep disturbance in coronary patients: "sleep onset and continuity disorder, " "disorder in daytime functioning, " "sleep disturbance caused by environmental factors, " "sleep disturbance as a result of cardiac diseases, " and "respiratory disorders during sleep." Furthermore, test-retest analysis showed a reliability correlation coefficient of r = 0.766 and α Cronbach's reliability (α = 0.855 ). Conclusion . Sleep disturbance questionnaire for patients with ACS hospitalized in coronary care unit (CCU) was identified in 5 dimensions and assessed for validity and reliability. To control and improve the sleep quality of CCU hospitalized patients, we need to identify and remove predisposing factors.